A dialysis accessory for attenuated total reflection infrared spectroscopy. Issue 3 (2006) - Krasteva Krasteva, Maria Maria; Kumar Kumar, Saroj Saroj; Barth Barth, Andreas Andreas
Abstract : A dialysis accessory for attenuated total reflection (ATR) infrared spectroscopy is described together with an evaluation based on known systems with well-studied infrared spectra, such as chemical oxidation and reduction of cytochrome c and substrate binding to the Ca 2+ -ATPase. Changes in the infrared spectra of the two proteins are successfully monitored with the dialysis accessory. The accessory was developed in our laboratory for the diamond 9-reflections SensIR ATR unit. It can be used to study absorbance changes of macromolecules which are induced by low molecular weight compounds, for example the binding of substrates, inhibitors or ions to macromolecules as well as effects of pH, ionic strength or denaturants on the structure of macromolecules. The dialysis accessory confines the macromolecule of interest to a sample compartment created between the ATR crystal and the dialysis membrane. On the other side of the dialysis membrane, a reservoir for the sample medium is created. In this way the low molecular weight compound of interest can exchange freely between the reservoir and the sample compartment via the dialysis membrane. This provides a flexible way to change sample conditions for the macromolecule of interest, allowing for example initiation of ligand binding.